Integrating corpus linguistics in second language vocabulary acquisition - Alruwaili, Awatif (2018)
Corpus linguistics has been used for over three decades in language teaching but not until now has it become a mainstream approach to language learning in the classroom. Thus, this thesis explores how the use of corpora can be successfully integrated into the English Foreign Language classroom, specifically in the Saudi classroom context. The integration is explored through two studies. Study One addresses the learners’ actual use of corpora in the classroom for learning general verbs patterns. General verbs patterns are selected through a multi-level approach which consists of a corpus-based approach as a first level, a phraseological approach as a second level and a pedagogical approach as a third level. The study relies on data collected from 51 participants who were at the intermediate level studying general English in the foundation year. The study ran for five weeks and included three training sessions, in which the learners were trained in how to use the corpus resource and how to read and analyse concordance lines and two testing sessions. The participants were tracked via software tracker in both training and testing sessions. The data were collected through tracking logs, activity sheets, reflective forms and interviews. The findings of Study One show that the intermediate-level learners were able to use the corpus resource in the same way as they had been trained, which indicates that the training was successful. The learners were also able to identify general verbs patterns through the use of concordance lines. Most participants had a positive attitude towards the use of corpora in the classroom besides identifying a few difficulties related to the use of corpora. Study Two investigates teachers’ attitudes towards the use of corpora in the classroom which included 56 in-service teachers who attended a training course on the uses of corpora in the classroom. The data collected included questionnaires (pre-course and post-course questionnaires) and interviews. The findings show that the questionnaires had a good reliability value and the teachers’ attitudes were moderately positive towards the use of corpora in the classroom. In addition, Study Two finds that there are some factors that seem to influence teachers’ attitudes, such as the training course, the level of computer literacy and the teachers’ perceptions of their role and learners’ roles within the communicative approach. The interviews constitute an in-depth investigation of teachers’ views about the use of corpora in the classroom by listing possible factors that facilitate or hinder the implementation of corpora in everyday teaching practice. Through the discussion of these findings from Study One and Study Two, a full integration of corpus linguistics into the Saudi classroom is possible taking into consideration the hindrances. These difficulties can be overcome through the offered proposal for implementing the use of corpora in the classroom.